Building Perceived Quality in the Influence of Personal Selling on Purchase Decision - Akbar, Taufiq (Interdisciplinary Social Studies, 2023)
Background: Personal selling is direct communication between payees and potential representatives that leads to profitable deals, customer satisfaction, and human relationships. Meanwhile, perceived quality is a consumer's perception of the overall quality or superiority of a product or service in relation to consumer decisions, and purchasing decisions are individual activities that are directly related to purchasing decisions for products or services offered by sellers. Aim: This study aims to analyze the influence of personal selling on purchasing decisions due to consumer perceptions of the quality of Tupperware products in Jayapura Regency. Method: This research is a quantitative research involving 184 customers. The data were analyzed by path analysis using the AMOS Structural Equation Model (SEM) program. Findings: The results showed that personal selling had a positive and significant effect on purchasing decisions (cr = 2.709: p = 0.007), personal selling had a positive and significant effect on perceived quality (cr = 2.278: p = 0.023 :), perceived quality had a positive and significant effect on purchasing decisions (cr = 1.784: p = 0.044) and personal selling had a positive and significant indirectly effect on purchasing decisions through perceived quality  (cr = 3.294: p = 0.003).